2012
DOI: 10.1007/s13197-012-0711-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of emulsion composition and spray-drying conditions on microencapsulation of tilapia oil

Abstract: The influence of processing conditions on the microencapsulation of tilapia oil by spray drying was studied. Trehalose, gelatin, sucrose and xanthan were used as emulsion composition. The experimental parameters of spray drying such as inlet air temperature, solid content, drying air flow rate and atomizing pressure were optimized using a central composite design. Encapsulation efficiency and lipid oxidation were determined. Bulk density, powder morphology and particle size were also analyzed. Trehalose improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Similar observations were made by Huang et al (2014), who demonstrated that trehalose addition to the walls of microcapsules caused an increase in ME compared to analogous samples with only saccharose as a carbohydrate component. Carneiro et al (2013) obtained ME in the range of 62.3 to 95.7% when flaxseed oil was encapsulated using a combination of maltodextrin with modified starches, whey protein Table 3 Loose bulk density (ρ L ), powder bulk density (ρ t100 ) tapped 100×, interstitial air content of loose powder (V ia L ) and powder tapped 100× (V ia 100 ), and Hausner index (HR 100 , HR 500 , and HR 1250 ) as a flowability concentrate, or gum Arabic.…”
Section: Free Oil Content Microencapsulation Efficiency and Oxidatisupporting
confidence: 85%
See 1 more Smart Citation
“…Similar observations were made by Huang et al (2014), who demonstrated that trehalose addition to the walls of microcapsules caused an increase in ME compared to analogous samples with only saccharose as a carbohydrate component. Carneiro et al (2013) obtained ME in the range of 62.3 to 95.7% when flaxseed oil was encapsulated using a combination of maltodextrin with modified starches, whey protein Table 3 Loose bulk density (ρ L ), powder bulk density (ρ t100 ) tapped 100×, interstitial air content of loose powder (V ia L ) and powder tapped 100× (V ia 100 ), and Hausner index (HR 100 , HR 500 , and HR 1250 ) as a flowability concentrate, or gum Arabic.…”
Section: Free Oil Content Microencapsulation Efficiency and Oxidatisupporting
confidence: 85%
“…They are able to inflate or expand and solidify with fewer indents on the surface. Similar spherical microcapsules of oil were produced in the following systems: OSA starch and trehalose or glucose syrup (Drusch et al 2006;Serfert et al 2009, Domian et al, 2015a, sodium caseinate or whey protein isolate with trehalose (Domian et al 2014), combinations of gelatin, xanthan, sucrose and trehalose (Huang et al 2014), and combinations of gum Arabic, maltodextrin DE 10, and whey protein isolate (Gallardo et al 2013). The structure of microcapsules presenting a rounded external surface with characteristic concavities may point to high viscoelasticity of the matrix, which was collapsing during drying.…”
Section: Resultsmentioning
confidence: 98%
“…Inlet air temperature significantly affects the MEE (Jafari et al, ). The research conducted by Huang et al () on microencapsulation of tilapia oil by spray drying revealed that an increase in inlet air temperature resulted in higher MEE because of rapid crust formation, making oil diffusion harder into particle surface. On contrary, Frascareli et al, claimed that faster drying of external surface area in high inlet air temperatures resulted in crack creation in coffee oil powder’s wall, leading to oil release and decreased the microencapsulated efficiency subsequently.…”
Section: Resultsmentioning
confidence: 99%
“…Ton et al (), Huang et al (), & Tonon et al () found out that MEE and POV altered oppositely in microencapsulation of rambutan seed oil, tilapia oil, and flaxseed oil by spray drying, respectively. Figure e indicates that peroxide value after was enhanced by increasing the feed pump rate.…”
Section: Resultsmentioning
confidence: 99%
“…RS has been used in combination with milk protein for preparation of fish oil capsules for in vitro lipolysis and their oxidative stability (Chung et al 2010). Oxidation of oils promotes the generation of free radicals leads to formation of unpleasant tastes and odours and reduces the shelf life of foodstuffs (Huang et al 2012). At first, fatty acids react with oxygen; produce odourless compounds, usually determined by PV test.…”
Section: Introductionmentioning
confidence: 99%